Grain size analysis from IODP Core 339-U1389A-11H - Stow, Dorrik A V; Smillie, Zeinab; Wilkin, Jonathan; Pan, Jiawei; Esegbue, Onoriode; Bahr, André; Ducassou, Emmanuelle (In: Stow, DAV et al. (2024): Sediment and geochemistry of bi-gradational contourite sequences from the Gulf of Cadiz [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.937307, 2024)
A total of 96 samples were analysed for bulk grain size from the two selected sequences, using a Malvern Mastersizer laser micro-granulometer (Malvern Panalytical) at the University of Bordeaux, France. The instrument is designed to measure the grain size spectrum ranging from 0.02 to 2000 μm (clay to sand).
Keywords: contourite; Contourites; grain size analysis; IODP 339; isotope analysis; U1389A